The Innovation of Consumption Code Innovation Set Off by The Sharing Economy：Xianyu Platform as An Example: 共享经济掀起的消费符码革新——以闲鱼为例 - FENG , Lang (Published by Confucius Institute UNS, 2022)
As a new economic phenomenon that has been hotly discussed in recent years, the sharing economy has shown the characteristics of being in line with the “The Fourth Consumption Era